2003
DOI: 10.1002/oti.180
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of mothers' and fathers' experience of parenting stress and attributions for parent–child interaction outcomes

Abstract: Parents of children with disabilities are vulnerable to parenting stress, which may place them at physical and psychological risk. However, it is not clear whether fathers experience stress differently to mothers, or whether their experiences are reported less frequently. Additionally, there is little reported on the relationships and gender differences between mothers' and fathers' attributions for parent child interaction outcomes. Parenting stress was assessed in this study using Abidin's (1990) Parenting S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 29 publications
(51 reference statements)
2
39
0
2
Order By: Relevance
“…Researchers in the area of family studies describe the birth of a baby as a significant transitional state that is intensified by having a child with a disability (Esdaile & Greenwood, 2003;Hornby, 1992;Pelchat et al, 2007). Historically it has been believed that the disability experience can only be a negative one for families (Risdal & Singer, 2004).…”
Section: Aaron Bonsallmentioning
confidence: 99%
“…Researchers in the area of family studies describe the birth of a baby as a significant transitional state that is intensified by having a child with a disability (Esdaile & Greenwood, 2003;Hornby, 1992;Pelchat et al, 2007). Historically it has been believed that the disability experience can only be a negative one for families (Risdal & Singer, 2004).…”
Section: Aaron Bonsallmentioning
confidence: 99%
“…8 Having a child with a disability or a chronic health condition has repeatedly been shown to increase parenting stress. [9][10][11][12][13][14] Dyson (2001) examined parental stress and family functioning in families with children with handicaps. She found that parental stress was high and was independent of economic and social constraints and that levels of stress did not affect family functioning.…”
Section: Introductionmentioning
confidence: 99%
“…This is the case in Tina's story where she expresses that 'I will never recover, there is no escape from the constant bereavement'. While several studies have established that parents of children with a disability, particularly mothers experience more stress, higher levels of anxiety (Esdaile and Greenwood, 2003;Estes et al, 2009;Seymour et al, 2013) increased sadness, a sense of denial and guilt (Ergu¨n and Ertem, 2012), and there is a need for health and social care professionals to proactively support families and listen to and value what they say and their knowledge of their child as this is essential to an effective working relationship (Blacher et al, 2005;Keen, 2007;Tomasello et al, 2010). Within Tina's story, she often felt isolated and alone and left feeling that the professionals avoided addressing the issue of her coping 'it surprised me that nobody could see my pain'.…”
Section: Resultsmentioning
confidence: 99%